The basic Philosophy behind and the Development of the EU Economic Air Transport Policy and other Policies which affect it - Sørensen, Frederik (Proceedings from the Annual Transport Conference at Aalborg University, 2001)
The European Communities were created in 1958 by the Treaty of Rome. Its institutions should guarantee that coherent decisions are taken, implemented and legally enforced in all Member States. Its general rules include, inter alia, provisions on right of establishment, freedom to provide services, competition, state aids and approximation of legislation. However, the Treaty included Article 84, which in its paragraph 2 stated that the Council could take any appropriate decision as to policy for air and sea transport. This was in contrast to what was stated in respect of the other modes of transport. On that basis practically everybody in air transport thought that until such a decision was taken air transport was excluded from Treaty provisions. Consequently while policy was developed for other modes of transport nothing happened in air transport until 1974. In this year the European Court of Justice took a decision concerning the application of social rules in the maritime sector. In this context the Court stated, contrary to the general belief, that the general provisions of the Treaty did apply to sea and air transport and that the exclusion contained in Article 84 only applied to the provisions contained in the transport chapter. It took some time for the Member States to get over the shock but in 1978 they had become convinced that an application of the general principles of the Treaty without attention being given to the specific characteristics of air transport would be too dangerous. They were also to some extent under the impression of the US deregulation, which came into effect in 1978. Therefore, a priority list for air transport was approved1 in 1978 by the Council. This was followed up in 1979 by a memorandum (the first) on air transport (A Community Approach) issued by the Commission. This was the start to a process where the European Union in the course of a number of years (14) developed an economic air transport policy for its internal market. This policy introduced, step by step, not only a liberal system but also safeguards and harmonization measures with a view to permit time for adaptation and to achieve a level playing field. As a consequence, essential provisions included in the bilateral agreements between the twelve Member States were therefore automatically replaced. This development is described in the following and also illustrated in annex 1. The liberalisation concerned the scheduled air transport but ultimately all types of air carriers were covered.